Diversifying Sources of Original Revenue (PAD) in South Bangka Through the Concept of Sport Tourism and Ecotourism Based on Local Uniqueness - Suhardi Suhardi (PT. Hafasy Dwi Nawasena, 2026)
This study aims to analyze the potential for diversification of Regional Original Income (PAD) in South Bangka Regency through the development of sports tourism and ecotourism concepts based on local uniqueness. The background of this research is based on the region's high dependence on conventional economic sectors such as mining, which are vulnerable to global fluctuations. The research method used is a qualitative approach with a descriptive-analytical type through data collection techniques such as interviews, observations, and documentation studies. The results of the study indicate that South Bangka Regency has great potential in tourism development, both through sport tourism based on sporting events such as beach and water sports, as well as ecotourism that utilizes mangrove ecosystems, coastal areas, and biodiversity. However, there are several major obstacles such as limited infrastructure, low quality human resources, suboptimal digital promotion, and the lack of systematic integration of tourism development planning. The discussion shows that the integration between sport tourism and ecotourism can be an effective strategy in increasing tourist attractions while creating sustainable economic impacts. The success of this sector's development depends heavily on synergy between the government, the community, and the private sector. Therefore, planned strategic policies, strengthening human resource capacity, increasing infrastructure investment, and innovation in digital-based promotion are needed. This research contributes to formulating a tourism development model based on local potential that can increase PAD sustainably and promote the welfare of local communities.